Позиціонування як метод створення професійного бренду в соцмережах - Лукаш, Галина (Видавництво Львівської політехніки, 2020)
The problem of analysis of social network tools in the process of its formationa professional brand is investigated. Positioning is characterized as one of the important methods of creating a professional brand. The significance of the image of a professional in social networks as a special market force is determined.
Keywords: імідж фахівця; професійний імідж; бренд; особисті стратегії